Biased Coupling to β-Arrestin of Two Common Variants of the CB2 Cannabinoid Receptor - Turu, Gábor; Soltész-Katona, Eszter; Tóth, András Dávid; Juhász, Cintia; Cserző, Miklós; Misák, Ádám; Balla, András; Caron, Marc G.; Hunyady, László (Frontiers in Endocrinology, 2021)
β-arrestins are partners of the G protein-coupled receptors (GPCRs), regulating their intracellular trafficking and signaling. Development of biased GPCR agonists, selectively targeting either G protein or β-arrestin pathways, are in the focus of interest due to their therapeutic potential in different pathological conditions. The CB2 cannabinoid receptor (CB2R) is a GPCR involved in various functions in the periphery and the central nervous system. Two common occurring variants of CB2R, harboring Q63R or L133I missense mutations, have been implicated in the development of a diverse set of disorders. To evaluate the effect of these mutations, we characterized the binding profile of these mutant CB2 receptors to G proteins and β-arrestin2. Although their ability to inhibit cAMP signaling was similar, the Q63R mutant had increased, whereas the L133I mutant receptor had decreased β-arrestin2 binding. In line with these observations, the variants also had altered intracellular trafficking. Our results show that two common variants of the CB2 receptor have biased signaling properties, which may contribute to the pathogenesis of the associated disorders and may offer CB2R as a target for further development of biased receptor activation strategies.